The Effects of Immigration in Developed Countries: Insights from Recent Economic Research - Anthony Edo; Lionel Ragot; Hillel Rapoport; Sulin Sardoschau; Andreas Steinmayr (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2018)
Immigrants currently account for 3.3% of the world's population. We know that migration is demographically important, but what are its implications for the labour market, public finance and political landscape? To answer these questions, this report draws on recent literature on the economic and cultural effects of immigration on host societies, with a focus on evidence for European countries. Although the average effects of immigration on labour markets and public finance are marginal, immigration can create winners and losers in the native workforce. By affecting the skill composition of receiving economies, an immigration-induced increase in the labour supply can impact wage dispersion in host countries. It is cultural concerns, however, that tend to fuel scepticism towards immigration, with fiscal or labour market playing only a secondary role. A deeper understanding of these concerns is a precondition for designing policies that foster a positive atmosphere and combat negative attitudes towards immigrants and extreme voting.
Keywords: 330